Method for manufacturing an electrode and its catalyst layer
By employing a mixture of large and small particle size catalysts in the electrode catalyst layer, the method enhances oxygen production efficiency and stability, addressing inefficiencies in existing oxygen generators.
Patent Information
- Application Number
- JP2022172166
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-27
- Filing Date
- 2022-10-27
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2042-10-27
AI Technical Summary
Existing oxygen generators face inefficiencies in oxygen production due to suboptimal catalyst selection and structure in the electrode catalyst layer, which affects redox reaction performance.
A manufacturing method involving a mixture of large and small particle size catalysts, conductive agents, and adhesives is used to create a catalyst layer with increased surface area through fluid channels, enhancing the oxygen production efficiency.
The method improves oxygen production efficiency by increasing the reaction area and stability of the electrode, resulting in higher current density and oxygen concentration.
Smart Images

Figure 0007604008000007 
Figure 0007604008000008 
Figure 0007604008000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an electrode and a catalyst layer thereof. Extreme The present invention relates to a method for producing the same and to a catalyst layer thereof. [Background technology]
[0002] A typical oxygen generator is a continuous oxygen supply device. The oxygen generator uses an electric motor (or air compressor) to input air from the ambient environment through a molecular sieve and separate the oxygen and nitrogen in the air, thereby obtaining high-concentration oxygen. The oxygen generator performs an oxidation-reduction reaction at the electrodes based on the principle of an electrochemical cell of metal and air, so that the oxygen generation efficiency decreases when oxygen from the ambient air is consumed at the cathode. Therefore, the material of the electrodes and its manufacturing method are important factors that affect the oxygen generation efficiency.
[0003] To perform a more efficient oxidation-reduction reaction, which catalyst should be selected as the material of the catalytic layer of the electrode has been the focus of research by those skilled in the art, since the activity of the catalyst has a great influence on the performance of the air electrode. In general, the air electrode is composed of a catalytic layer containing a catalyst, a conductive current collector, and a gas diffusion membrane. The inventor of the present invention focuses on how to select and utilize the catalytic layer material to improve the oxygen generation efficiency of the oxygen generator. DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a method for manufacturing an electrode that improves the structure of an electrode catalyst layer, increases the reaction area, and improves the efficiency of oxygen generation. [Means for solving the problem]
[0005] According to the above concept, a method for manufacturing an electrode is proposed, which includes the steps of mixing a first catalyst having a first average particle size, a second catalyst having a second average particle size, a first conductive agent, a first adhesive, and a solvent to form a first mixture, in which the weight ratio of the first catalyst to the first catalyst is 5:1 to 1:5, stirring the first mixture to obtain a second mixture, rolling the second mixture into a catalyst layer, and laminating the catalyst layer, a conductive current collector, and a gas diffusion membrane to obtain an electrode.
[0006] Further, in accordance with the above concept, a method for manufacturing an electrode has been proposed, which includes the steps of mixing a catalyst, a first conductive agent, a first adhesive, and a solvent to form a first mixture, the catalyst including a relatively large particle size catalyst and a relatively small particle size catalyst, stirring the first mixture to obtain a second mixture, rolling the second mixture into a catalyst layer, and laminating the catalyst layer, a conductive current collector, and a gas diffusion membrane to obtain an electrode.
[0007] According to the above concept, a catalyst layer of an electrode is proposed, which comprises a relatively large particle size catalyst, a relatively small particle size catalyst, a conductive agent and an adhesive, the relatively large particle size catalyst has a first average particle size, the relatively small particle size catalyst has a second average particle size, and the first average particle size is larger than the second average particle size. [Brief description of the drawings]
[0008] The above embodiments and advantages of the present invention will become more readily apparent to those skilled in the art after reviewing the following detailed description and accompanying drawings. [Figure 1] FIG. 2 is an enlarged schematic view showing the structure of a catalyst layer of an electrode according to one embodiment of the present invention. [Diagram 2] 1 is a flowchart illustrating the manufacture of an electrode including a catalyst layer in an embodiment of the present invention. [Figure 3A] FIG. 2 is a schematic diagram showing an electrode structure according to one embodiment of the present invention. [Figure 3B] FIG. 4 is a schematic diagram illustrating an electrode structure according to another embodiment of the present invention. [Figure 4] FIG. 1 is a schematic diagram showing the structure of an oxygen generating device in which tests were conducted using the electrodes of Examples 1 to 5 of the present invention and the comparative example. [Diagram 5] 1 is a line graph showing changes in current density per unit area with respect to time in Examples 1 to 5 of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] When reading the following detailed description, please refer to all figures of the present invention. All figures of the present invention show different embodiments of the present invention by illustrating examples, and help those skilled in the art understand how to implement the present invention. This example provides sufficient embodiments to demonstrate the spirit of the present invention, and each embodiment is not inconsistent with other embodiments, and new embodiments can be implemented through any combination thereof. That is, the present invention is not limited to the embodiments disclosed in this specification.
[0010] FIG. 1 is a schematic diagram showing an enlarged structure of a catalyst layer of a cathode according to an embodiment of the present invention. In FIG. 1, the catalyst layer 100 mainly includes a conductive agent 101, an adhesive 102, a large catalyst 103, and a small catalyst 104. The conductive agent 101 is uniformly distributed in the adhesive 102 and on the surface of the large catalyst 103 and the small catalyst 104. The adhesive 102 also fixes the large catalyst 103 and the small catalyst 104 together, but there are fluid channels 105 in the catalyst layer 100, between the large catalyst 103, between the small catalyst 104, and between the large catalyst 103 and the small catalyst 104. The fluid channels 105 also have larger or smaller sizes, respectively. The catalyst layer 100 according to an embodiment of the present invention has a structure in which the large catalyst 103 and the small catalyst 104 are mixed. The large fluid channels 105 are formed by the large particle size catalyst 103, and the small fluid channels 105 are formed by the small particle size catalyst 104, so that the fluid channels 105 are densely distributed within the catalyst layer, which can increase the surface area of the catalyst, improve the reaction efficiency, and improve the oxygen production efficiency.
[0011] In the catalyst layer 100 according to the embodiment of the present invention, the catalyst as the main component includes a large particle catalyst 103 and a small particle catalyst 104, and "particle size" means "average particle size". "Average particle size" refers to the arithmetic mean or D50 value (i.e., the median value of the particle size distribution) calculated by a laser particle size analyzer known to those skilled in the art. "Average particle size" can be determined as needed by those skilled in the art. For example, in order to keep the quality of the product stable, catalyst particles of an appropriate particle size are sieved with a sieve having a specific mesh according to the requirements. In addition, since the shape of the catalyst particles is not constant, the particle size is calculated based on the relatively long diameter of the particles. The average particle size range of the large particle catalyst 103 of the present invention is 150-270 μm, and the average particle size range of the small particle catalyst 104 is 5-50 μm. The average particle size of the large particle catalyst 103 is 3-54 times larger than the average particle size of the small particle catalyst 104.
[0012] In the catalyst layer 100 according to an embodiment of the present invention, either the large particle size catalyst 103 or the small particle size catalyst 104 comprises a material selected from the group consisting of ruthenium dioxide, iridium dioxide, manganese dioxide, cobalt oxide, tricobalt tetroxide, nickel hydroxide, nickel oxide, iron oxide, tungsten trioxide, vanadium pentoxide and palladium oxide.
[0013] The adhesive 102 includes a material selected from the group consisting of polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP), and polyvinylidene fluoride (PVDF). The conductive agent 101 includes a material selected from the group consisting of carbon black, acetylene black, and carbon nanofibers.
[0014] FIG. 2 is a flow chart showing the manufacturing of an electrode including a catalyst layer 100 according to an embodiment of the present invention. In step (S1), a large particle catalyst 103, a small particle catalyst 104, a conductive agent 101, an adhesive 102 and a solvent are mixed to form a first mixture. In step (S2), the first mixture is stirred to obtain a second mixture. In step (S3), the second mixture is rolled into a catalyst layer to obtain the catalyst layer 100. The solvent is water, alcohol or a combination thereof. Then, to manufacture the catalyst layer 100 into an electrode, the solvent is evaporated and discharged during the electrode manufacturing process, which helps to generate fluid channels 105, such as pores, in the catalyst layer 100. The manufacturing method further includes a step (S4) of stacking the catalyst layer 100, a conductive current collector and a gas diffusion membrane to obtain an electrode.
[0015] The amount of the conductive agent 101 added in the above step (S1) does not exceed half of the total weight of the first mixture, and is preferably in the range of 20 to 50%, and more preferably in the range of 28 to 46%. The conductive agent 101 can increase the conductivity of the electrode. If the amount of the conductive agent 101 added is too large, the catalyst content decreases and the reaction ability decreases. The catalyst added in the above step (S1) has a weight ratio of large particle catalyst to small particle catalyst of 10:1 to 1:10, preferably 5:1 to 1:5.
[0016] The difference between the mixing step (S1) and the stirring step (S2) is that the step (S1) is a rough mix and does not require high uniformity, whereas the step (S2) is carried out to achieve high uniformity of the mixture. Therefore, in the mixing step (S1), the rotation speed may be 50 to 800 rpm, preferably 100 to 700 rpm, and more preferably 150 to 600 rpm. A mixer (blade shear mixer) that is commonly used by those skilled in the art can be used to produce the first mixture. In the stirring step (S2), a planetary mixer (also called a gravity centrifugal mixer) can be used, and the rotation speed is set in the range of 200 to 2000 rpm, preferably 400 to 1900 rpm, and more preferably 500 to 1400 rpm to produce the second mixture. In addition, the step (S2) is not limited to the use of a planetary mixer, and can also be carried out by a blade shear mixer as long as the purpose of uniformly dispersing the materials can be achieved.
[0017] The rolling step (S3) can be carried out using a rolling machine commonly used by those skilled in the art, and the rotation speed is set in the range of 1 to 30 rpm, preferably 2 to 28 rpm, and more preferably 4 to 26 rpm, and the roller temperature is set to less than 150°C, preferably 15 to 100°C, and more preferably 20 to 80°C.
[0018] FIG. 3A is a schematic diagram showing an electrode structure according to one embodiment of the present invention. FIG. 3B is a schematic diagram showing an electrode structure according to another embodiment of the present invention. As shown in FIG. 3A, the cathode 113 is formed by laminating a conductive current collector 112 on the catalyst layer 100, and laminating a gas diffusion membrane 111 on the conductive current collector 112. Also, as shown in FIG. 3B, a first gas diffusion membrane 111a is laminated on the catalyst layer 100, then a conductive current collector 112 is laminated on the first gas diffusion membrane 111a, and finally a second gas diffusion membrane 111b is laminated on the conductive current collector 112. The four-layered electrode has good bonding between the gas diffusion membrane 111 and the conductive current collector 112, so that a more stable reaction can be obtained than with a three-layered structure.
[0019] The function of the conductive current collector 112 is to concentrate the current, fix the catalyst layer, and support the electrode structure. The conductive current collector 112 is a metal mesh or foam having a material selected from the group consisting of stainless steel, nickel, titanium, and copper. The function of the gas diffusion membranes 111, 111a, and 111b is to allow oxygen to pass through and prevent the electrolyte from leaking out. The gas diffusion membranes 111, 111a, and 111b are made of the same material as the conductive agent 101 and the adhesive 102. That is, the gas diffusion membranes 111, 111a, and 111b are made of a conductive agent and an adhesive. The conductive agent is, for example, selected from one or at least one of carbon black, acetylene black, and carbon nanofiber. The adhesive is selected from one of polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP), and polyvinylidene fluoride (PVDF). The gas diffusion membranes 111, 111a, and 111b are manufactured by mixing, stirring, and rolling. The manufacturing process of the gas diffusion membranes 111, 111a, and 111b is similar to steps S1 to S3 except that no catalyst is added, and a person skilled in the art can adjust the mixing ratio as necessary. The ratio of the conductive agent 101 is preferably higher than the ratio of the adhesive 102. In the gas diffusion membrane 111, the ratio of the adhesive 102 is higher than the ratio of the catalyst layer 100.
[0020] Based on the above-mentioned manufacturing method of the catalyst layer 100 of the present invention, a related embodiment is proposed as follows.
[0021] [Table 1]
[0022] Example 1 of the present invention was prepared according to the ratios in Table 1 above. Specifically, 45 g of MnO2 with an average particle size of 270 μm, 9 g of MnO2 with an average particle size of 5 μm, 103.5 g of XC72R, and 67.5 g of PTFE were mixed with 112 g of 95% ethanol and 665 g of water, and stirred at 200 rpm for 10 minutes in a DLH DC mixer (manufactured by YOTEC, MRB-3500L) to produce a gelatinous first mixture after thorough mixing. The gelatinous first mixture was then stirred at 1900 rpm for 5 minutes in a planetary mixer (manufactured by THINKY) to obtain an accumulated second mixture. The accumulated second mixture was then rolled into a catalyst layer with a thickness of 0.78 mm using a roller compactor (manufactured by EKTRON TEK, EKT-2100SLM) at 25° C. and 50 rpm. Finally, the catalyst layer was laminated with a conductive current collector and a gas diffusion membrane (thickness 1.2 mm) to obtain a 1.87 mm thick electrode or cathode).
[0023] [Table 2]
[0024] Example 2 of the present invention was prepared according to the ratios in Table 2 above. Specifically, 78.75 g of MnO2 with an average particle size of 270 μm, 15.75 g of MnO2 with an average particle size of 50 μm, 56.25 g of XC72R, 6.75 g of VGCF-H, and 67.5 g of PTFE were mixed with 112 g of 95% ethanol and 665 g of water, and stirred at 200 rpm for 10 minutes in a DLH DC mixer (manufactured by YOTEC, MRB-3500L) to produce a gelatinous first mixture after thorough mixing. Next, the gelatinous first mixture was stirred at 1900 rpm for 5 minutes in a planetary mixer (manufactured by THINKY) to obtain an accumulated second mixture. The accumulated second mixture was then rolled into a catalyst layer with a thickness of 0.78 mm using a roller compactor (EKTRON TEK, EKT-2100SLM) at 25° C. and 50 rpm. Finally, the catalyst layer was laminated with a conductive current collector and a gas diffusion membrane (thickness 1.2 mm) to obtain an electrode or cathode with a thickness of 1.87 mm.
[0025] [Table 3]
[0026] Example 3 of the present invention was prepared according to the ratios in Table 3 above. Specifically, 78.75 g of MnO2 with an average particle size of 150 μm, 15.75 g of MnO2 with an average particle size of 5 μm, 85.5 g of XC72R, and 45 g of PTFE were mixed with 114 g of 95% ethanol and 662 g of water, and stirred in a DLH DC mixer (YOTEC, MRB-3500L) at 200 rpm for 10 minutes to produce a gelatinous first mixture after thorough mixing. The gelatinous first mixture was then stirred in a planetary mixer (THINKY) at 1900 rpm for 5 minutes to obtain an accumulated second mixture. The accumulated second mixture was then rolled into a catalyst layer with a thickness of 0.78 mm using a roller compactor (EKTRON TEK, EKT-2100SLM) at 25° C. and 50 rpm. Finally, the catalyst layer was laminated with a conductive current collector and a gas diffusion membrane (thickness 1.2 mm) to obtain a 1.87 mm thick electrode or cathode).
[0027] [Table 4]
[0028] Example 4 of the present invention was prepared according to the ratios in Table 4 above. Specifically, 67.5 g of MnO2 with an average particle size of 150 μm, 13.5 g of MnO2 with an average particle size of 50 μm, 99 g of XC72R, and 45 g of PTFE were mixed with 114 g of 95% ethanol and 662 g of water, and stirred in a DLH DC mixer (YOTEC, MRB-3500L) at 200 rpm for 10 minutes to produce a gelatinous first mixture after thorough mixing. The gelatinous first mixture was then stirred in a planetary mixer (THINKY) at 1900 rpm for 5 minutes to obtain an accumulated second mixture. The accumulated second mixture was then rolled into a catalyst layer with a thickness of 0.78 mm using a roller compactor (EKTRON TEK, EKT-2100SLM) at 25° C. and 50 rpm. Finally, the catalyst layer was laminated with a conductive current collector and a gas diffusion membrane (thickness 1.2 mm) to obtain a 1.87 mm thick electrode or cathode).
[0029] [Table 5]
[0030] Example 5 of the present invention was prepared according to the ratios in Table 5 above. Specifically, 13.5 g of MnO2 with an average particle size of 150 μm, 67.5 g of MnO2 with an average particle size of 50 μm, 69.75 g of XC72R, 6.75 g of VGCF-H, and 67.5 g of PTFE were mixed with 112 g of 95% ethanol and 665 g of water, and stirred at 200 rpm for 10 minutes in a DLH DC mixer (manufactured by YOTEC, MRB-3500L) to produce a gelatinous first mixture after thorough mixing. The gelatinous first mixture was then stirred at 1900 rpm for 5 minutes in a planetary mixer (manufactured by THINKY) to obtain an accumulated second mixture. The accumulated second mixture was then rolled into a catalyst layer with a thickness of 0.78 mm using a roller compactor (manufactured by EKTRON TEK, EKT-2100SLM) at 25° C. and 50 rpm. Finally, the catalyst layer was laminated with a conductive current collector and a gas diffusion membrane (thickness 1.2 mm) to obtain a 1.87 mm thick electrode or cathode).
[0031] [Table 6]
[0032] Comparative examples of the single average particle size of the present invention were prepared according to the ratios in Table 6 above. Specifically, 45.0 g of MnO2 with a single average particle size of 150 μm (similar to Examples 1 to 5 above, the single average particle size refers to the D50 value calculated by a laser particle size analyzer known in the art), 112.5 g of XC72R, 67.5 g of PTFE, 112 g of 95% ethanol, and 665 g of water were mixed at 200 rpm for 10 minutes in a DLH DC mixer (manufactured by YOTEC, MRB-3500L) and mixed thoroughly to prepare a gelatinous first mixture. Next, the gelatinous first mixture was stirred at 1900 rpm for 5 minutes in a planetary mixer (THINKY Corporation) to obtain an accumulated second mixture. The accumulated second mixture was then rolled into a catalyst layer with a thickness of 0.78 mm using a roller compactor (EKTRON TEK, EKT-2100SLM) at 25° C. and 50 rpm. Finally, a conductive current collector and a gas diffusion membrane (with a thickness of 1.2 mm) were laminated onto the catalyst layer to obtain an electrode (or cathode) with a thickness of 1.87 mm.
[0033] FIG. 4 is a schematic diagram showing the configuration of an oxygen generating device tested using the electrodes of Examples 1 to 5 and Comparative Example. In order to test the effect of electrodes made of different materials, a simplified oxygen generating device 200 is proposed. As shown in FIG. 4, in a container 116 having an electrolyte 115 (30% sodium hydroxide), a part of the cathode 113 is manufactured according to the manufacturing process of the above Examples and Comparative Example, and a nickel mesh used as the anode 114 is placed inside the container 116. In the container 116, the catalyst layer 100 of the cathode 113 and the anode 114 are immersed in the electrolyte 115. The gas diffusion layer 111 of the cathode 113 is placed outside the container 116, and the catalyst layer 100 is inside the container 116, so that oxygen in the atmosphere can enter the container 116 through the gas diffusion layer 111. When a voltage is applied to the oxygen generator 200, an electrochemical reaction occurs between the catalyst layer 100 and the anode 114 to generate highly concentrated oxygen from oxygen in the air, and the oxygen generator 200 can concentrate the oxygen in the air, which is only 19%, to 80% or more. The surface area of the cathode 113 and the anode 114 is 100 cm 2 Therefore, it can be used in a portable oxygen generator. During the test, a voltage of 1 V was applied to the electrode to measure the current value, and the current value was divided by the area to obtain the current density value. The results are shown in Figure 5.
[0034] FIG. 5 is a line graph showing the change in the relationship between the current density per unit area and time for Examples 1-5 of the present invention and Comparative Example. The higher the current density per unit area, the higher the electrochemical reaction capacity, and therefore the oxygen generation efficiency of the electrode of the embodiment of the present invention can be evaluated. This test was carried out by combining the cathode of the embodiments 1-5 with potassium hydroxide electrolyte and anode Ni mesh. In FIG. 5, it can be seen that the current densities per unit area in the embodiments 1-5 obtained by the catalysts having two average particle sizes of the present invention are all larger than the current density obtained by the catalysts having a single average particle size in the comparative example. As for the effect of Example 1, it is not as good as the comparative example in the first hour, but after 1 hour the effect gradually increases, and after 3 hours it approaches the effect of Examples 4 and 5. That is, because the ratio of adhesive and catalyst is different, the starting value of each embodiment is also different, but the final result is better than the catalysts with a single average particle size range. From FIG. 5, it can be seen that the effect of Example 3 is obviously the best.
[0035] Although the present invention has been described above using the embodiments, the technical scope of the present invention is not limited to the scope described in the above embodiments. It is clear to those skilled in the art that various modifications and improvements can be made to the above embodiments. It is clear from the description of the claims that such modifications and improvements can also be included in the technical scope of the present invention. [Explanation of symbols]
[0036] 100 catalyst layer 101 Conductive agents 102 Adhesive 103 Large particle catalyst 104 Small particle size catalyst 105 Fluid Channel 111 Gas diffusion layer 111a first gas diffusion membrane 111b Second gas diffusion membrane 112 Conductive collector 113 Cathode 114 Anode 115 Electrolyte 116 Container 200 Oxygen Generator S1~S4 process
Claims
1. A method for producing an electrode for an oxygen generator, comprising the steps of: mixing a first catalyst having a first average particle size in the range of 150-270 μm, a second catalyst having a second average particle size in the range of 5-50 μm, a first conductive agent, a first adhesive, and a solvent to form a first mixture, wherein the weight ratio of the first catalyst to the second catalyst is 5:1 to 1:5; agitating the first mixture to obtain a second mixture; rolling the second mixture into a catalyst bed; and a step of laminating a conductive current collector on the catalyst layer, and laminating a gas diffusion membrane on the conductive current collector to obtain an electrode for an oxygen generator;
2. the gas diffusion membrane includes a second conductive agent and a second adhesive; Either the first catalyst or the second catalyst comprises a material selected from the group consisting of ruthenium dioxide, iridium dioxide, manganese dioxide, cobalt oxide, cobalt tetroxide, nickel hydroxide, nickel oxide, iron oxide, tungsten trioxide, vanadium pentoxide, and palladium oxide; Either the first conductive agent or the second conductive agent comprises a material selected from the group consisting of carbon black, acetylene black, and carbon nanofibers; Either the first adhesive or the second adhesive comprises a material selected from the group consisting of polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP) and polyvinylidene fluoride (PVDF); the solvent is water, an alcohol, or a combination thereof; 2. The method for manufacturing an electrode for an oxygen generator according to claim 1, wherein the conductive current collector is a metal mesh or foam having a material selected from the group consisting of stainless steel, nickel, titanium, and copper.
3. a rotation speed in either the mixing in the step of forming the first mixture or the stirring in the step of obtaining the second mixture is 100 to 2000 rpm; The stirring includes at least one of a gravity centrifugal stirring process and a blade shear stirring process, 2. The method for producing an electrode for an oxygen generator according to claim 1, wherein the step of laminating a conductive current collector on the catalyst layer and laminating a gas diffusion membrane on the conductive current collector uses a roller device under conditions of a rolling speed of less than 30 rpm and a temperature of less than 150° C.
4. 2. The method for producing an electrode for an oxygen generator according to claim 1, wherein the first average particle size is 3 to 54 times the second average particle size.
5. A method for producing an electrode for an oxygen generator, comprising the steps of: mixing a catalyst, a first conductive agent, a first adhesive, and a solvent to form a first mixture, the catalyst including a relatively large particle size catalyst and a relatively small particle size catalyst, the relatively large particle size catalyst having an average particle size of 150-270 μm, and the relatively small particle size catalyst having an average particle size of 5-50 μm; agitating the first mixture to obtain a second mixture; rolling the second mixture into a catalyst bed; and a step of laminating a conductive current collector on the catalyst layer, and laminating a gas diffusion membrane on the conductive current collector to obtain an electrode for an oxygen generator;
6. the gas diffusion membrane includes a second conductive agent and a second adhesive; Either the relatively large particle size catalyst or the relatively small particle size catalyst comprises a material selected from the group consisting of ruthenium dioxide, iridium dioxide, manganese dioxide, cobalt oxide, cobalt tetroxide, nickel hydroxide, nickel oxide, iron oxide, tungsten trioxide, vanadium pentoxide, and palladium oxide; Either the first conductive agent or the second conductive agent comprises a material selected from the group consisting of carbon black, acetylene black, and carbon nanofibers; Either the first adhesive or the second adhesive comprises a material selected from the group consisting of polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP) and polyvinylidene fluoride (PVDF); the solvent is water, an alcohol, or a combination thereof; 6. The method for manufacturing an electrode for an oxygen generator according to claim 5, wherein the conductive current collector is a metal mesh or foam having a material selected from the group consisting of stainless steel, nickel, titanium, and copper.
7. a rotation speed in either the mixing in the step of forming the first mixture or the stirring in the step of obtaining the second mixture is 100 to 2000 rpm; The stirring includes at least one of a gravity centrifugal stirring process and a blade shear stirring process, 6. The method for producing an electrode for an oxygen generator according to claim 5, wherein the steps of laminating a conductive current collector on the catalyst layer and laminating a gas diffusion membrane on the conductive current collector have a rolling speed of less than 30 rpm and a temperature of less than 150° C.
8. 6. The method for producing an electrode for an oxygen generator according to claim 5, wherein the average particle size of the relatively large particle size catalyst is 3 to 54 times the average particle size of the relatively small particle size catalyst.
9. A catalytic layer of an electrode for an oxygen generator, A relatively large particle size catalyst, a relatively small particle size catalyst, a conductive agent, and an adhesive, The relatively large particle size catalyst has a first average particle size, the first average particle size being 150 to 270 μm; the relatively small particle size catalyst has a second average particle size, the second average particle size being between 5 and 50 μm; The weight ratio of the relatively large particle size catalyst to the relatively small particle size catalyst is 5:1 to 1:5; A catalyst layer of the oxygen generator electrode.
10. the first average particle size is 3 to 54 times the second average particle size; Either the relatively large particle size catalyst or the relatively small particle size catalyst comprises a material selected from the group consisting of ruthenium dioxide, iridium dioxide, manganese dioxide, cobalt oxide, cobalt tetroxide, nickel hydroxide, nickel oxide, iron oxide, tungsten trioxide, vanadium pentoxide, and palladium oxide; the conductive agent comprises a material selected from the group consisting of carbon black, acetylene black, and carbon nanofibers; 10. The catalyst layer of the oxygen generator electrode according to claim 9, wherein the adhesive comprises a material selected from the group consisting of polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP) and polyvinylidene fluoride (PVDF).
Citation Information
Patent Citations
Porous transport layer based on plurality of sintered porous layers
EP3686318A1
Gas diffusion electrode
JP1994093488A
Polymer solid electrolyte film / Electrode integrally molded body and manufacture thereof
JP1996329962A
Membrane electrode assembly for fuel cell
JP2008004453A
Photocatalyst electrode, method for manufacturing the same and hydrogen generator
JP2014118594A
